An Analysis of Language Attitude on Denny Caknan’s Instagram Comments: A Sociolinguistics Study - Galuh Kharisma Devi (SEMINAR NASIONAL SOSIAL, SAINS, PENDIDIKAN, HUMANIORA (SENASSDRA), 2023)
Language attitude is an important thing that must be considered to maintain the continuity of a language. One of the interesting uses of language to observe is comments on public figures' social media accounts. Data analysis in this study used theory from Garvin & Mathiot (1968). The theory explains that there are three characteristics in language attitude, namely; (1) Language Loyalty, Language Pride, and Awareness of the Norm. The purpose of this study was to analyze the language attitude used by the public on social media. The research method used by researchers is qualitative descriptive. The results of this study show that most of Denny Caknan's followers have the language attitude that is dominated by language pride.